Transcending the “Black Raven”: An Autoethnographic and Intergenerational Exploration of Stalinist Oppression - Krahn, Elizabeth (Qualitative Sociology Review, 2013)
Many of Canada’s aging immigrants were displaced persons in Europe post-WWII and have internalized psychological effects of their traumatic past within a society that tends to marginalize or pathologize them. While early collective trauma literature focuses on individualized, psychotherapeutic approaches, more recent literature demonstrates the importance of externalizing and contextualizing trauma and fostering validating dialogue within families and community systems to facilitate transformation on many levels. My research is an autoethnographic exploration of lifespan and intergenerational effects of trauma perceived by Russian Mennonite women who fled Stalinist Russia to Germany during WWII and migrated to Winnipeg, Canada, and adult sons or daughters of this generation of women. Sixteen individual life narratives, including my own, generated a collective narrative for each generation. Most participants lost male family members during Stalin’s Great Terror, verschleppt, or disappeared in a vehicle dubbed the Black Raven. Survivors tended to privilege stories of resilience – marginalizing emotions and mental weakness. The signature story of many adult children involved their mother’s resilience, suppressed psychological issues, and emotional unavailability. Results underline the importance of narrative exchange that validates marginalized storylines and promotes individual, intergenerational, and cultural story reconstruction within safe social and/or professional environments, thus supporting healthy attachments.